Pengembangan Multimedia Interaktif Berbasis Problem-Based Learning Pada Pembelajaran IPAS di Sekolah Dasar - Fikry, Dicky Wahyudi; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This study aims to produce an interactive multimedia Articulate Storyline 3 (PBL) based on science learning in grade IV elementary schools that is valid, practical and also effective. This type of research is development research (R&D) using the ADDIE model which has five steps, namely: analysis, design, development, implementation, and evaluation. The developed learning media was validated by the validator and the practicality of the product was tested by filling out the teacher's and student's response questionnaires. The results of the science learning media research obtained a very valid category with a validity level of 90% for the media aspect, 84% for the material aspect, and 90% for the language aspect. The results of teacher and student responses in research schools show that the use of interactive multimedia Articulate Storyline 3 is very practical with a percentage of teacher responses of 98% and 97.8% of students. The results of the effectiveness of learning media show very effective results with an increase in the percentage of student learning outcomes of 86.08% and 92% completeness. It can be concluded that Articulate Storyline 3-based interactive multimedia (PBL) in science learning in class IV elementary school has been declared valid, practical, and effective for use in the learning process.